Nephrotic Syndrome and Idiopathic Membranous Nephropathy Associated with Autosomal-Dominant Polycystic Kidney Disease - Ramón Peces; Jorge Martínez-Ara; Carlos Peces; Mariluz Picazo; Emilio Cuesta-López; Cristina Vega; Sebastián Azorín; Rafael Selgas (The Scientific World Journal)
We report the case of a 38-year-old male with autosomal-dominant polycystic kidney disease (ADPKD) and concomitant nephrotic syndrome secondary to membranous nephropathy (MN). A 3-month course of prednisone 60 mg daily and losartan 100 mg daily resulted in resistance. Treatment with chlorambucil 0.2 mg/kg daily, low-dose prednisone, plus an angiotensin-converting enzyme inhibitor (ACEI) and an angiotensin II receptor blocker (ARB) for 6 weeks resulted in partial remission of his nephrotic syndrome for a duration of 10 months. After relapse of the nephrotic syndrome, a 13-month course of mycophenolate mofetil (MFM) 2 g daily and low-dose prednisone produced complete remission for 44 months. After a new relapse, a second 24-month course of MFM and low-dose prednisone produced partial to complete remission of proteinuria with preservation of renal function. Thirty-six months after MFM withdrawal, complete remission of nephrotic-range proteinuria was maintained and renal function was preserved. This case supports the idea that renal biopsy is needed for ADPKD patients with nephrotic-range proteinuria in order to exclude coexisting glomerular disease and for appropriate treatment/prevention of renal function deterioration. To the best of our knowledge, this is the first reported case of nephrotic syndrome due to MN in a patient with ADPKD treated with MFM, with remission of proteinuria and preservation of renal function after more than 10 years. Findings in this patient also suggest that MFM might reduce cystic cell proliferation and fibrosis, preventing progressive renal scarring with preservation of renal function.